Ecological insights into the Frillfin Goby in Badagry Creek, Lagos, Nigeria - O. Lawson Emmanuel; E. Thomas Ajibola (Advances in Aquaculture and Fisheries Management, 2023)
A study was conducted in Badagry Creek in Lagos, Nigeria on food and feeding habits and reproduction of Frillfin goby (Bathygobius soporator). Data collected from the study intend to serve as a baseline for carrying out further study on the fishes and fisheries of this water body. B. soporator is one of the numerous and diverse fishes of the family Gobiidae which share certain similarities in their life histories. Gobies are among the most successful fishes. They are resident intertidal species which could be found in pools, rocky pools, lagoons, creeks and estuaries. Specimens were collected from the Badagry Creek via Oto-Awori Fish Jetty between January, 2008 and January, 2009. Foods and feeding habits and reproduction were studied in this creek. Seven groups of food items were encountered in the stomachs of the fish, viz; Crustaceans, Pisces, Insects, Detritus, Bivalves, unidentified food materials and Gastropods. The most eaten of these were the crustaceans contributing 34% by number and 38.30% by frequency of occurrence. The presence of other fish species in the stomachs explained the piscivorous habit while the unidentified food materials demonstrate its herbivorous character. Its predatory and carnivorous tendency was exhibited by the presence of insects, bivalves, crustaceans, and gastropods. Presence of sand grains was an indicator of its benthic nature. The specimens were classified as either male or female. Four hundred and seventy and five specimens representing 98.95 and 1.05% of total catch were classified as males and females, respectively giving 1 (male): 0.01 (female) sex ratio. This is significantly different (P>0.05) from the expected or theoretical one male:one female ratio and not in conformity with sex ratios that were reported for some fishes in the adjacent Ologe, Lagos, Lekki and Epe lagoons which favoured more females. The Gonadosomatic index (GSI) of this species varied from 0.00 to 2.89%, meaning less than 2.89% of the fish’s body mass was converted to gonads for reproduction. The pre-spawning and spawning stages of this species contributed 86.75 and 13.25% of the specimens, respectively. Post spawning stages were absent.